Homoclinic Orbit in a Six Dimensional Model of a Perturbed Higher-order NLS Equation (Journal of Partial Differential Equations, 2003)
" In this paper, the perturbed higher-order NLS equation with periodic boundary condition is considered. The existence of the homoclinic orbits for the truncation equation is established by Melnikov analysis and geometric singular perturbation theory."
Keywords: homoclinic; higher-order NLS equation; perturbation